WEB site recruitment in counseling and clinical psychology: an exploratory evaluation of multicultural content - Chambers, Serenity, author; Chavez, Ernest L., advisor; Borrayo, Evelinn A., committee member; De Miranda, Michael A., committee member; Swaim, Randall C., committee member (Colorado State University. Libraries, 2006)
The multicultural movement in Psychology calls for racial/ethnic parity in its graduate student representation. One method of increasing minority student representation is to foster a multicultural graduate program. The current study explored the extent to which the multicultural development of a program as portrayed by its Web site affected prospective students' attraction to the program. Participants were contacted via email through their Department of Psychology or Psi Chi chapter, and were randomly assigned to a Web site of a fictitious graduate program in Counseling/Clinical Psychology, representing one of the four multicultural levels. Participants included 134 prospective graduate students in Counseling or Clinical Psychology (78.4% female, 18.7% male) who were at the junior level or above. Minority-identified participants made up 26.9% of the sample. Participants were asked to view the Web site of the fictitious graduate program as if it were real, after which they completed the online Prospective Student Survey, which assessed their attraction for the program. A factor analysis of the Prospective Student Survey yielded two components. Factor scores were calculated and used as dependent variables in subsequent analyses. Employing a MANOV A with an alpha level of 0.05 yielded a significant main effect for multicultural level. Post-hoc tests revealed significant differences for General Affinity Scores (p < 0.05), suggesting that prospective students preferred graduate programs with low and high levels of multicultural development to the placebo. No differences were found between minority and non-minority students. Overall, results suggest a relationship between the information presented on a graduate program's Web site and a prospective student's attraction for that program. Namely, prospective students value programs with either no multicultural emphasis or with multiculturalism integrated throughout. The disregard of the placebo program suggests that a Web site containing very little information is unattractive to prospective students. Congruent with past studies, the results imply that program materials, namely information presented on Web sites, can and should be used as a cost-efficient recruitment tool. To help psychology programs in this endeavor, a list of 12 components to include on Web sites is stipulated.
Zip file contains dataset materials.
Keywords: Minority graduate students; Psychology -- Study and teaching (Graduate); Web sites